Tea Leaf Picking Tool "Apedat" With an Automatic System Controlled by DC Motor - Laili, Reni (Altifani Journal: International Journal of Community Engagement, 2021)
Pagaralam is a mountainous region with chilly temperatures, many of which have been cultivated with tea and coffee plants by the locals. These tea and coffee trees flourish, making them a dependable source of revenue for the local community. Obstacles in the field include conventional equipment for picking tea leaves, which slow down the harvesting process, as well as slippery and steep road conditions. This makes it more difficult for employees to reach the leaves that need to be plucked using standard equipment. One of the ways to enhance the added value for the community (partners) in terms of agricultural yields is to develop instruments that are more practical, quick, and ergonomic, and needless human work. The procedure entails designing and introducing a tea leaf picker powered by a dc motor. Based on the findings of field experiments, technologies can be developed to accelerate and increase the quantity of harvest. The community (partners) can sense a considerable boost in efficiency and effectiveness.